Clinical evidence of acupuncture for amnestic mild cognitive impairment: A systematic review and meta-analysis of randomized controlled trials - Guangyao Lin; Stella Lim Jin Yie; Shanshan Guo; Xuanling Li; Lianwei Xu (Complementary Therapies in Medicine)
Background: People with amnestic mild cognitive impairment (aMCI) carry a substantial risk of developing dementia compared to non-amnestic MCI (naMCI). Several previous studies proved the remarkable effectiveness of acupuncture for MCI, but they didn't distinguish between aMCI and naMCI. We conducted this meta-analysis to systematically assess the evidence of the efficacy of acupuncture in this unique population with aMCI. Methods: We comprehensively searched nine databases on January 09, 2024, to identify relevant articles estimating the effects of acupuncture for aMCI, and then assessed the risk of bias of the included trials utilizing the RoB 2.0 tool which included the domain of randomization process, deviation from intended interventions, missing outcome data, measurement of the outcome, selection of the reported outcome, and overall bias. The results of this meta-analysis were exhibited with forest plots. Sensitivity analyses were conducted to determine the robustness of the pooled results, and publication bias was estimated by Egger's and Begg's tests. Besides, we also performed subgroup analysis to determine whether there was a difference in therapeutic effects between four weeks and eight weeks of treatment duration. The certainty of the evidence was graded using GRADEpro GDT. Results: A total of 15 randomized controlled trials (RCTs) involving 908 people with aMCI were included in this study. According to the meta-analysis, acupuncture treatment provided a remarkable improvement in cognitive function as assessed by Mini-Mental State Examination (MD = 1.09, 95 %CI [0.86, 1.31], p < 0.00001), Montreal Cognitive Assessment (MD = 0.93, 95 %CI [0.80, 1.07], p < 0.00001), Alzheimer's Disease Assessment Scale-Cognitive (MD = 1.00, 95 %CI [-1.23, −0.77], p < 0.00001), and P300 latency (MD = −15.40, 95 %CI [-23.68, −7.12], p = 0.0003). Subgroup analysis showed evidence that the efficacy of four weeks of acupuncture treatment was consistent with that of eight weeks. Sensitivity analyses, Egger's and Begg's tests suggested the pooled results were robust and reliable. The overall quality of the evidence, as appraised by the GRADE criteria, was very low or low for all outcomes. Conclusions: The evidence from 15 RCTs demonstrated that acupuncture interventions are effective in ameliorating cognitive function in people with aMCI. There is a need for larger-scale multicenter RCTs using standardised training protocols and more rigorous designs to confirm the conclusions further. Registration: This study was registered in the International Prospective Register of Systematic Reviews (PROSPERO). The registration number is CRD42023460470.